The Valuation of Risk Assets and the Selection of Risky Investments in Stock Portfolios and Capital Budgets: A Comment - Haley, Charles W. (The Review of Economics and Statistics, 1969)
Charles W. Haley, The Valuation of Risk Assets and the Selection of Risky Investments in Stock Portfolios and Capital Budgets: A Comment, The Review of Economics and Statistics, Vol. 51, No. 2 (May, 1969), pp. 220-221